Production, Purification, and Characterization of Thermostable Alkaline Xylanase From Anoxybacillus kamchatkensis NASTPD13 - Yadav, Punam (Front Bioeng Biotechnol, 2018)
Anoxybacillus kamchatkensis NASTPD13 used herein as a source for thermostable alkaline xylanase were isolated from Paudwar Hot Springs, Nepal. NASTPD13 cultured at 60°C, pH 7 and in presence of inorganic (ammonium sulfate) or organic (yeast extract) nitrogen sources, produced maximum xylanase enzyme. Xylanase production in the cultures was monitored by following the ability of culture media to hydrolyze beech wood xylan producing xylooligosaccharide and xylose by thin layer chromatography (TLC). The extracellular xylanase was isolated from optimized A. kamchatkensis NASTPD13 cultures by ammonium sulfate (80%) precipitation; the enriched xylanase preparation was dialyzed and purified using Sephadex G100 column chromatography. The purified xylanaseshowed 11-fold enrichment with a specific activity of 33 U/mg and molecular weight were37 kDa based on SDS-PAGE and PAGE-Zymography. The optimum pH and temperature of purified xylanase was 9.0 and 65°C respectively retainingmore than 50% of its maximal activity over a broad range of pH (6–9) and temperature (30–65°C). With beech wood xylan, the enzyme showed Km 0.7 mg/ml and Vmax 66.64 μM/min/mg The xylanase described herein is a secretory enzyme produced in large quantities by NASTPD13 and is a novel thermostable, alkaline xylanase with potential biotechnological applications.